+0  
 
0
8
1
avatar+1679 

Solve the inequality (x - 2)(x + 6) \le (x - 2)(x + 5). Write your answer in interval notation.

 Feb 14, 2024

Best Answer 

 #1
avatar+1622 
+2

\((x-2)(x+6)\le(x-2)(x+5)\)

\(x^2+4x-12 {{\le}} x^2+3x-10\)

\(4x-12{\le}3x-10\)

\(x{\le}2\)

 

Be careful when you divide by x - 2, because it can remove a possible solution, and also mess with the inequality sign!

Your answer in interval notation is (-inf, 2]

 Feb 14, 2024
 #1
avatar+1622 
+2
Best Answer

\((x-2)(x+6)\le(x-2)(x+5)\)

\(x^2+4x-12 {{\le}} x^2+3x-10\)

\(4x-12{\le}3x-10\)

\(x{\le}2\)

 

Be careful when you divide by x - 2, because it can remove a possible solution, and also mess with the inequality sign!

Your answer in interval notation is (-inf, 2]

proyaop Feb 14, 2024

2 Online Users

avatar
avatar